Improvement of Oral Bioavailability of Curcumin upon Microencapsulation with Methacrylic Copolymers - Paolino, Donatella; Vero, Ada; Cosco, Donato; Pecora, Tiziana M. G.; Cianciolo, Simona; Fresta, Massimo; Pignatello, Rosario (Frontiers in Pharmacology, 2016)
Curcumin (diferuloymethane; CUR) is a yellow pigment used in traditional medicine throughout history for its anti-inflammatory activity. In the last years, the scientific research has demonstrated that CUR effects are related to the modulation of crucial molecular targets, related to several pathologies including cancer, arthritis, diabetes, Crohn’s disease. In this paper, two formulations of microencapsulated CUR obtained by coevaporation with polymethacrylate polymers (Eudragit® Retard) were investigated in vitro, ex vivo and in vivo, and results were compared by laser confocal microscopy analysis. The permeation of microencapsulated CUR through CaCo-2 monolayers was evaluated in vitro. The mucoadhesion and bioadhesion of the CUR-loaded microparticles were evaluated in vitro, using E12 and CaCo-2 human intestinal cells, and ex vivo, by means of excised rat intestinal mucosa. After oral administration to rats, microencapsulated CUR showed a 7-fold increase of bioavailability in respect to the neat drug, with a concomitant reduction of the Tmax and a 5-fold plasma concentration peak increase.